Effects of glucanase treatment on the structure and mechanical properties of cell walls in the giant‐celled xanthophycean alga Vaucheria frigida. Issue 1 (25th September 2018) - Mine, Ichiro; Oda, Sahori; Sekida, Satoko
Summary: The cell wall of the tip‐growing cells of the giant‐cellular xanthophycean alga Vaucheria frigida is mainly composed of cellulose microfibrils (CMFs) arranged in random directions and the major matrix component into which the CMFs are embedded throughout the cell. The mechanical properties of a cell‐wall fragment isolated from the tip‐growing region, which was inflated by artificially applied pressure, were measured after enzymatic removal of the matrix component by using a protease; the results showed that the matrix component is involved in the maintenance of cell wall strength. Since glucose and uronic acid are present in the matrix component of Vaucheria cell walls, we measured the mechanical properties of the cell wall after treatment with endo‐1, 3‐ß‐glucanase and observed the fine structures of its surfaces by atomic force microscopy. The major matrix component was partially removed from the cell wall by glucanase, and the enzyme treatment significantly weakened the cell wall strength without affecting the pH dependence of cell wall extensibility. The enzymatic removal of the major matrix component by using a protease released polysaccharide containing glucose and glucuronic acid. This suggests that the major matrix component of the algal cell walls contains both proteins (or polypeptides) and polysaccharides consisting of glucose and glucuronic acid as the main constituents.